Identifikasi Lokasi Potensial Panen Air Hujan Menggunakan Indeks Kesesuaian Embung dan Sistem Informasi Geografi di Provinsi Jawa Timur Indonesia: Identification of Locations for Potential Rainwater Harvesting Using the Conformity Index of Embankments and Geographic Information Systems in East Java Province, Indonesia - Santikayasa, I Putu; Syarifah, Mauludiyyatus; Taufik, Muh (Jurnal Teknik Sipil dan Lingkungan, 2021)
Increasing population has an impact on increasing food supply to fulfil the requirement of the community. Increasing in food supply is able to be achieved by increasing the agricultural productive area. Low-water agricultural technology is one of technology can be applied in the development of agricultural areas with sufficient water availability. But on the other hand, water harvesting technology using pond is one approach in the development of agricultural land in dry areas. This study uses a geographic information system (GIS) approach to identify areas that have high potential for the development of water harvesting ponds in East Java Province, Indonesia. GIS approaches is used for spatial analysis in calculating the area potential index for the ponds deveopment based on climate, physical surface and vegetation indicators. This index is calculated based on indicators, each of which is obtained from the surface parameter data. The results of the study show that the East Java Province is categorized as the "very suitable" and "appropriate" areas on water harvesting ponds suitability by 55% and 23%, respectively. This results show that the potential of the East Java area for developing water harvesting pond is very high about 78% compared with the entire region. On the other hand, locations that is categorized as "not suitable" and "very inappropriate" are about 8.7% and 9.2% compared with total area of ​​East Java Province. Iit can be concluded that climate, physical surface and vegetation indicators are very important in determining the locations of water harvesting ponds development in East Java Province.